Understanding the photocatalytic mechanisms of the BiOI/Bi2MoO6 and BiOCl/Bi2MoO6 heterostructures: First-principles study. (November 2020) - Zhou, Guoli; Tian, Zhixue; Sun, Honggang; Zhang, Junmeng; Zhao, Huiyan; Li, Pan; Sun, Huiyuan
Abstract: First-principles calculations are used to explore the interfacial structures and photocatalytic mechanisms of the BiOI/Bi2 MoO6 and BiOCl/Bi2 MoO6 heterostructures. We find that both the BiOI/Bi2 MoO6 and BiOCl/Bi2 MoO6 composites have small lattice mismatch and good stability. The DOS analysis show that the BiOI/Bi2 MoO6 belongs to type-II heterostructure, while the BiOCl/Bi2 MoO6 composite is a type-I heterostructure. The analyses of the electron difference density and Mulliken charge suggest that charge transferring and redistribution occurs at the interfaces. Moreover, a built-in electric field directed from Bi2 MoO6 to BiOI or BiOCl can be formed at the interfaces of the heterostructures. The band alignment and built-in electric field in the BiOI/Bi2 MoO6 and BiOCl/Bi2 MoO6 heterostructures can promote the separation of the photo-generated carriers, resulting in their improved photocatalytic activities compared with the single component. Our work may provide useful information for understanding the photocatalytic mechanisms of the BiOI/Bi2 MoO6 and BiOCl/Bi2 MoO6 heterostructures and developing more efficient heterostructure photocatalysts. Graphical abstract: Image 1 Highlights: Both the BiOI/Bi2 MoO6 and BiOCl/Bi2 MoO6 composites have small lattice mismatch and good stability. BiOI/Bi2 MoO6 belongs to type-II heterostructure, while the BiOCl/Bi2 MoO6 composite is a type-I heterostructure. A built-in electric field directed from Bi2 MoO6 to BiOI or BiOCl can be formed at the interfaces of the heterostructures. The band alignment and built-in electric field can promote the separation of the photo-generated carriers.